Concordance of Dye-Spraying Chromoendoscopy and Virtual Chromoendoscopy for Colonic Dysplasia Detection in Longstanding Inflammatory Bowel Disease - Correia, João Paulo Laranjeira; Ponte, Ana; Proença, Luisa; Rodrigues, Adélia; Pinho, Rolando; Leite, Sónia; Fernandes, Carlos; Rodrigues, Jaime; Silva, João Carlos; Gomes, Catarina; Afecto, Edgar; Estevinho, Maria Manuela; et al. (Turkish Journal of Gastroenterology, 2023)
Background/Aims: In the past, dye-spraying chromoendoscopy was the technique of choice for colonic surveillance in patients with long-standing extensive inflammatory bowel disease. Recent evidence suggests that virtual chromoendoscopy is an equally acceptable technique. Materials and Methods: Eleven gastroenterologists were given a survey with 20 pairs of pictures from inflammatory bowel disease surveillance colonoscopies (10 with nondysplastic lesions, 5 with dysplastic lesions, and 5 with no lesions). Each pair contained the same image captured during colonoscopy using indigo carmine and narrow-band imaging. For each picture, the gastroenterologist assessed the presence/absence of lesion and, when a lesion was identified, assessed the presence/absence of dysplasia and delineated its margins. To compare lesion and dysplasia detection between techniques, sensitivity, specificity, and interobserver agreement were calculated. The chi-square test was used to assess the accuracy of margins delineation. Results: When assessing lesion and dysplasia detection, similar sensitivity and specificity values were obtained for both techniques. Interobserver agreement analysis revealed that dye-spraying chromoendoscopy and virtual chromoendoscopy had a moderate agreement in lesion detection but, for dysplasia detection, dye-spraying chromoendoscopy had a slight agreement [K = 0.11 (0.03-0.18), P < .01] and virtual chromoendoscopy a fair agreement [K = 0.30 (0.22-0.37), P < .01]. Margin delineation was similar between techniques. Conclusion: Sensitivity and specificity for lesion and dysplasia detection, as well as the accuracy of margins delineation, were similar between dye-spraying chromoendoscopy and virtual chromoendoscopy. Interobserver agreement for dysplasia detection was suboptimal in both techniques; however, it was superior when using virtual chromoendoscopy. These findings suggest that virtual chromoendoscopy constitutes a valid alternative for dysplasia screening in inflammatory bowel disease. Cite this article as: Correia JPL, Ponte A, Proença L, et al. Concordance of dye-spraying chromoendoscopy and virtual chromoendoscopy for colonic dysplasia detection in longstanding inflammatory bowel disease. Turk J Gastroenterol. 2023;34(11):1150-1155.